Pyraclostrobin impairs energetic mitochondrial metabolism and productive performance of silkworm (lepidoptera: Bombycidae) caterpillars - Nicodemo, Daniel [UNESP]; Mingatto, Fábio Ermínio [UNESP]; De Carvalho, Amanda [UNESP]; Bizerra, Paulo Francisco Veiga [UNESP]; Tavares, Marco Aurélio [UNESP]; Balieira, Kamila Vilas Boas [UNESP]; Bellini, William Cesar [UNESP] (Oxford University Press (OUP), 2018)
Silkworm cocoon production has been reduced due to a number of problems other than those inherent in sericulture, such as diseases, malnutrition, and inappropriate management. The use of pesticides in areas surrounding mulberry fields can contaminate these plants and consequently harm caterpillars. The aim of this study was to evaluate whether the application of the fungicide pyraclostrobin in mulberry plants interferes with the mitochondrial bioenergetics and the productive performance of silkworms. Mulberry plants were treated with pyraclostrobin (0, 100, 200, and 300 g ha-1). After 30 d of fungicide application, fifth instar caterpillars were fed with leaves from the treated plants. We evaluated in vitro and in vivo mitochondrial bioenergetics of mitochondria from the head and intestines, as well as the feed intake and mortality rate of the caterpillars and the weight of fresh cocoons and cocoons shells. At doses of 50 μM (in vitro) and 200 g ha-1 (in vivo), pyraclostrobin inhibited oxygen consumption in state 3, dissipated membrane potential, and inhibited ATP synthesis in mitochondria. Pyraclostrobin acted as a respiratory chain inhibitor, affecting mitochondrial bioenergetics. The fungicide did not interfere with food consumption but negatively affected mortality rate and weight of cocoons. Mulberry leaves contaminated with pyraclostrobin negatively impact the mitochondrial bioenergetics of silkworms and cocoon production.
Keywords: Cocoon; Fungicide; Mitochondria; Mulberry; Strobilurin